Association between executive and food functions in the acute phase after stroke - Mourão, Aline Mansueto; Vicente, Laélia Cristina Caseiro; Abreu, Mery Natali Silva; Chaves, Tatiana Simões; Sant'Anna, Romeu Vale; Braga, Marcela Aline Fernandes; Meira, Fidel Castro Alves de; Souza, Leonardo Cruz de; Miranda, Aline Silva de; Rachid, Milene Alvarenga; Teixeira, Antçnio Lucio (Arquivos de Neuro-Psiquiatria, 2018)
Purpose To investigate potential associations among executive, physical and food functions in the acute phase after stroke.Methods This is a cross-sectional study that evaluated 63 patients admitted to the stroke unit of a public hospital. The exclusion criteria were other neurological and/or psychiatric diagnoses. The tools for evaluation were: Mini-Mental State Examination and Frontal Assessment Battery for cognitive functions; Alberta Stroke Program Early CT Score for quantification of brain injury; National Institutes of Health Stroke Scale for neurological impairment; Modified Rankin Scale for functionality, and the Functional Oral Intake Scale for food function.Results The sample comprised 34 men (54%) and 29 women with a mean age of 63.6 years. The Frontal Assessment Battery was significantly associated with the other scales. In multivariate analysis, executive function was independently associated with the Functional Oral Intake Scale.Conclusion Most patients exhibited executive dysfunction that significantly compromised oral intake.
Keywords: stroke; cognitive dysfunction; cognition